2018
DOI: 10.1080/0284186x.2018.1440085
|View full text |Cite
|
Sign up to set email alerts
|

Confounders other than comorbidity explain survival differences in Danish and Swedish ovarian cancer patients – a comparative cohort study

Abstract: Danish OC patients have a poorer prognosis than patients in Sweden but the difference in survival seems to be explained by other factors than comorbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…A meta-analysis of eight prospective studies involving more than 12,000 patients demonstrated an increased mortality risk in patients with concomitant diseases (HR 1.2, 95% CI 1.11–1.3) [ 13 ]. Noer et al (2018) confirmed that comorbidity was significantly associated with worse overall survival HR 1.36 (1.05–1.77), p = 0.020 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of eight prospective studies involving more than 12,000 patients demonstrated an increased mortality risk in patients with concomitant diseases (HR 1.2, 95% CI 1.11–1.3) [ 13 ]. Noer et al (2018) confirmed that comorbidity was significantly associated with worse overall survival HR 1.36 (1.05–1.77), p = 0.020 [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experts have investigated molecular and genetic changes in different histological types of OC to provide a specific target therapy [ 10 ]. In addition, many studies have addressed comorbidity and its correlation with ovarian cancer survival [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Cardiovascular diseases and diabetes may contribute directly to increased mortality in OC patients and indirectly through treatment selection, suboptimal surgery, and chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…To test this hypothesis, more than 3,100 patients from the Danish and Swedish Gynecologic clinical registries were studied with demonstration of comparable comorbidities. Though concomitant diseases negatively influence survival, this parameter could not explain the observed survival differences between the countries [80].…”
Section: Benchmark Studiesmentioning
confidence: 80%
“…Other major types originate from stromal cells (5%) and germ cells (3%) [50]; to this end, many rare subtypes are linked to specific outcomes [51]. The poor prognosis is due to a long period of asymptomatic cancer growth with delayed detection in (very) advanced stages [45][46][47], severe comorbidity in elderly, lack of patient centralization, and differences in disease treatment management and disease biological profile [52][53][54][55][56]. Global miRNA expression analysis of serous and clear cell ovarian carcinomas identifies differentially expressed miRNAs including miR-200c-3p as a prognostic marker [57].…”
Section: Ovarian Cancermentioning
confidence: 99%